The Role of Franchise Concept In Entrepreneurship (In Context of Indian Corporate World): Analyzing the Feasibility of Franchise Model in the Indian Corporate Environment (Journal of Advances and Scholarly Researches in Allied Education, 2012)
To study the concept offranchise model and perform feasibility study of franchise model in context ofIndian subcontinent. In addition, to develop a Franchise Disclosure Document(FDD) suitable for Indian corporate environment.